KETERAMPILAN DASAR BERMAIN SEPAKBOLA PADA SISWA PUTRA SD INPRES MANGGA DUA KABUPATEN MERAUKE - Dwi Kuswoyo , Dili; Jondry Hiskya, Hendra; Margaretha Warwuru, Priciliya (Indonesian Journal of Physical Education and Sport Science, 2023)
Study Purpose. This study discusses the problem of the level of football skills of male students aged 10-12 years at SD Inpres Mangga Dua, Merauke Regency. The purpose of this study was to determine the level of soccer skills of male students aged 10-12 years at SD Inpres Mangga Dua Merauke Regency. The population in this study were all male students aged 10-12 years of SD Inpres Mangga Dua Merauke Regency totaling 35 students. Materials and methods. The instrument used was the 10-12 year old football skills test from Daral Fauzi R. To determine the level of football skills using six test items, namely: 1) dribbling, 2) short pass, 3) throw in, 4) running with the ball, 5) heading, and 6) shooting at the goal. The data analysis technique used in this study was descriptive statistics. Results. The results showed that the level of soccer skills of male students aged 10-12 years at SD Inpres Mangga Dua, Merauke Regency, with the number of students with a classification of excellent = 7 people (20%), good = 9 people (25.71%), moderate = 11 people (31.42%), less 3 people (8.57%), and very less 5 people (14.28%).Conclusion. The results of this study can be concluded that the development of children aged 10-12 is very good.